ANALISIS KORELASI ANTARA RESPON MAHASISWA TERHADAP PEMBELAJARAN BERBASIS NEURO LINGUISTICS PROGRAMMING (NLP) TIPE REFRAMING DENGAN MOTIVASI BELAJAR MATEMATIKA MAHASISWA SEMESTER VII IAIN SYEKH NURJATI CIREBON - ade sudjana; Reza Oktiana Akbar (Jurusan Tadris Matematika UIN Siber Syekh Nurjati Cirebon, 2014)
A fun learning is one of ways to increase students’ learning motivation. Generally,students tend not to have learning motivation, because they do not understand delivered material. With a new learning, it will ease lecturers to deliver materials to students. One of ways which can be used in order to understand the materials is with re-framing perception activity based on neuro linguistics programming (NLP) reframing type. The goal of this research is to know the students’ response towards linear programming learning based on Neuro-Linguistics Programming Reframing Type, to know learning motivation of linear programming based on Neuro-Linguistics Programming Reframing Type and to know how big students’ response towards linear programming learning based on Neuro-Linguistics Programming Reframing Type in relation to learning motivation. In doing learning activity, everyone needs a certain demand in order to get learning achievement in learning activity as the goals which expected. One of factors which demands students is motivation. This research uses quantitative approach with analysis method and data collecting technique using questionnaire. This research takes an amount of same population and sample 48 students of Semester VII from class B of IAIN Syekh Nurjati Cirebon in Linear Programming Course. The data processing uses normalitas test, homogeneity test, correlation test and hypothesis test. Based on calculation result, score of tcount is2,29, meanwhile score of ttable is 2,01. So, score of tcount > ttable (2,29 > 2,01), so that H0is rejected and Ha is accepted. It means there is significant influence towards students’motivation given treatment with Method of Neuro-Linguistics Programming (NLP)reframing type in linear programming discussion. Key Words : NLP, fun learning, learning motivation